THE IMPACT OF ENTREPRENEURIAL ORIENTATION ON SMEs PERFORMANCE IN GHANA: THE ROLE OF SOCIAL CAPITAL AND GOVERNMENT SUPPORT POLICIES - Solomon Gbene Zaato; Mohammad Ismail; Sathiswaran Uthamaputhran; Wilberforce Owusu-Ansah (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2020)
The primary purpose of this study was to propose a conceptual framework on the impact of entrepreneurial orientation (EO) on SMEs performance in Ghana: The role of social capital (SC) and government support policies (GSPs). The study reviewed existing literature pertaining the five dimensions of EO and used measures of SC, and GSPs in relation to SMEs performance in Ghana. This study would be anchored on two theories thus the resource-based view and the social capital theories stressing the need for SMEs to focus more on their unique resources that existed within their social network relations. The study would further provide new insight to practitioners to understand and appreciate the role of SC and GSPs on SMEs performance